Base Editing in Human Cells to Produce Single‐Nucleotide‐Variant Clonal Cell Lines. Issue 1 (5th November 2020) - Vasquez, Carlos A.; Cowan, Quinn T.; Komor, Alexis C.
Abstract: Base‐editing technologies enable the introduction of point mutations at targeted genomic sites in mammalian cells, with higher efficiency and precision than traditional genome‐editing methods that use DNA double‐strand breaks, such as zinc finger nucleases (ZFNs), transcription‐activator‐like effector nucleases (TALENs), and the clustered regularly interspaced short palindromic repeats (CRISPR)–CRISPR‐associated protein 9 (CRISPR‐Cas9) system. This allows the generation of single‐nucleotide‐variant isogenic cell lines (i.e., cell lines whose genomic sequences differ from each other only at a single, edited nucleotide) in a more time‐ and resource‐effective manner. These single‐nucleotide‐variant clonal cell lines represent a powerful tool with which to assess the functional role of genetic variants in a native cellular context. Base editing can therefore facilitate genotype‐to‐phenotype studies in a controlled laboratory setting, with applications in both basic research and clinical applications. Here, we provide optimized protocols (including experimental design, methods, and analyses) to design base‐editing constructs, transfect adherent cells, quantify base‐editing efficiencies in bulk, and generate single‐nucleotide‐variant clonal cell lines. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Design and production of plasmids for base‐editing experiments Basic Protocol 2 : Transfection of adherent cells and harvesting of genomic DNA Basic Protocol 3 : Genotyping of harvested cells using Sanger sequencing Alternate Protocol 1 : Next‐generation sequencing to quantify base editing Basic Protocol 4 : Single‐cell isolation of base‐edited cells using FACS Alternate Protocol 2 : Single‐cell isolation of base‐edited cells using dilution plating Basic Protocol 5 : Clonal expansion to generate isogenic cell lines and genotyping of clones